Declining Discount Rates - Cropper, Maureen L.; Freeman, Mark C.; Groom, Ben; Pizer, William A. (American Economic Review, 2014)
We ask whether the US government should replace its current discounting practices with a declining discount rate schedule, as the United Kingdom and France have done, or continue to discount the future at a constant exponential rate. We present the theoretical basis for a declining discount rate (DDR) schedule, but focus on how, in practice, a DDR could be estimated for use by policy analysts. We discuss the empirical approaches in the literature and review how the United Kingdom and France estimated their DDR schedules. We conclude with advice on how the United States might proceed to consider modifying its current discounting practices.